Efficacy of Brucella abortus S19 and RB51 vaccine strains: A systematic review and meta‐analysis. Issue 4 (14th August 2021) - de Oliveira, Marina Martins; Pereira, Carine Rodrigues; de Oliveira, Izabela Regina Cardoso; Godfroid, Jacques; Lage, Andrey Pereira; Dorneles, Elaine Maria Seles
Abstract: This systematic review and meta‐analysis aimed to recalculate the efficacy of Brucella abortus S19 and RB51 vaccine strains and discuss the main variables associated with controlled trials to evaluate bovine brucellosis vaccine efficacy (VE). The most commonly used vaccine strain was S19, at a dose of 10 10 colony forming units (CFU), followed by RB51 at 10 10 CFU. The most commonly used challenge strain was B. abortus 2308, at a dose of 10 7 CFU, by the intraconjunctival route. Regarding the meta‐analysis, trials were grouped according to the vaccine strain and dose to recalculate protection against abortion (four groups) or infection (five groups) using pooled risk ratio (RR) and VE. Regarding protection against abortion ( n = 15 trials), the S19 vaccine at 10 9 CFU exhibited the highest protection rate (RR = 0.25, 95% confidence interval (CI) : 0.12–0.52; VE = 75.09%, 95% CI: 48.08–88.05), followed by RB51 at 10 10 CFU (RR = 0.31, 95% CI: 0.16–0.61; VE = 69.25%, 95% CI: 39.48–84.38). Regarding protection against infection ( n = 23 trials), only two subgroups exhibited significant protection: S19 at 10 9 CFU (RR = 0.28, 95% CI: 0.14–0.55; VE = 72.03%, 95% CI: 57.70– 81.50) and RB51 at 10 10 CFU (RR = 0.43, 95% CI: 0.22–0.84; VE = 57.05%, 95% CI: 30.90–73.30). In conclusion, our results suggest that a dose of 10 9 CFU for S19 and 10 10 CFU for RB51 are the most suitable for the prevention of abortion and infection caused by B. abortus .